Theoretical Study of Tautomeric Conformations for 1,2,4-Triazole Derivatives - Mahboub, Radia (2021)
We have performing theoretical calculations of the 1,2,4-triazole derivatives using DFT B3LYP method to study the tautomeric conformations of 1,2,4-triazole-3-thiol (TL 2A and TL 2C) and 1,2,4-triazole-3-thione (TL 2B) derivatives. Then, we compare the obtained results to methyltriazole thioether (MTE 1). The full geometry optimizations were carried out using 6-31G basis set. The frontier orbital energy, atomic net charges were discussed. DOI: http://dx.doi.org/10.17807/orbital.v13i1.1582